PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI, DAN KEADILAN ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL PADA CV.MEGAH FOOD TRADING - Permatasari, Kadek Chintya; Supartha, Wayan Gede (E-Jurnal Manajemen; Vol 6 No 8 (2017), 2017)
Organizational commitment is very important for the survival of an organization, because with the commitment that exists between individuals and organizations it can create a sense of ownership of the organization and can build the organization. This study aims to determine the influence of transformational leadership, organizational culture and organizational justice towards organizational commitment. This research was conducted on employees CV.Megah Food Trading. The sample of this research is 35 respondents with saturated sampling method. In this study data collection is done by distributing questionnaires using Likert scale. The technique used in this research is multiple linear regression. Based on the results of the analysis, this study shows 1) Transformational leadership has a positive and significant impact on organizational commitment on CV.Megah Food Trading. 2) Organizational culture has a positive and significant effect on organizational commitment on CV.Megah Food Trading. 3) organizational justice has a positive and significant effect on organizational commitment on CV.Megah Food Trading.